The effectiveness of Jigsaw cooperative learning model in developing students’ oral communication skills and cognitive learning outcomes - Median Agus Priadi; Tri Jalmo; Darlen Sikumbang; Kartika Meilinda (Assimilation: Indonesian Journal of Biology Education, 2022)
This study aims to determine the effectiveness of Jigsaw cooperative learning model in developing communication skills and cognitive learning outcomes of students. This research using the one group pretest-posttest design. The sample is the students of class X MIA 1 who were selected through purposive sampling technique. Data on oral communication skills were carried out by self-assessment, peer assessment and observation which were analyzed using a Likert scale. Meanwhile, data on cognitive learning outcomes were obtained through pretest and posttest scores, then analyzed by performing the n-gain score test. The research data shows that students have oral communication skills in the "high" category, which is as much as 77%. The highest verbal communication skills of students are found in the indicator of delivering detailed information with the "very high" category, while the lowest communication skills are found in the indicator of giving questions in the "enough" category. Then for learning outcomes, statistically student learning outcomes showed a significant difference between initial understanding (pretest) and understanding after learning (posttest) indicated by a significant N-gain value of 0.73 with high criteria. Thus, it can be concluded that the Jigsaw cooperative learning model is effective in developing communication skills and cognitive learning outcomes of students.